2017
DOI: 10.2320/matertrans.mbw201609
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Phase Formation Rate during In-Field Solid-Phase Reactive Sintering of Mn-Bi

Abstract: Microstructural analysis was performed for Mn-Bi prepared by in-eld solid-phase reactive sintering, in order to investigate the origin of magnetic eld effects on the reaction. The number of formed MnBi phase around Mn grain in 10 T was almost 3 times larger than that in a zero eld. The results indicated that the magnetic eld enhanced the phase formation rate of MnBi phase. Due to the enhancement of the phase formation rate, the fraction of MnBi phase was drastically increased by in-eld annealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…The gain of Zeeman energy influences the reactions in ferromagnetic systems. 12,13) Previously, we reported the magnetic-field enhancement of the reaction of ferromagnetic MnBi, pointing out that the contribution of a small Zeeman energy of less than 0.25 kJ/mol reduced the activation energy by about 4 kJ/ mol. 13) In addition, the ineffectiveness of magnetic fields on liquid-solid reactions of a Mn-Ga system was found, which was probably due to the competition between reductions of activation energy and the pre-exponential factor.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The gain of Zeeman energy influences the reactions in ferromagnetic systems. 12,13) Previously, we reported the magnetic-field enhancement of the reaction of ferromagnetic MnBi, pointing out that the contribution of a small Zeeman energy of less than 0.25 kJ/mol reduced the activation energy by about 4 kJ/ mol. 13) In addition, the ineffectiveness of magnetic fields on liquid-solid reactions of a Mn-Ga system was found, which was probably due to the competition between reductions of activation energy and the pre-exponential factor.…”
Section: Discussionmentioning
confidence: 94%
“…and a reduction of activation energy. 12,13) Crystallization of an ferromagnetic phase from an amorphous form under magnetic fields has been also studied. 14,15) Field-induced enhancement of nucleation of Fe-Si-B was explained by the magnetic field reducing the critical radius of the crystallized nuclei and the activation energy.…”
Section: High Magnetic Field Effects On the Solid-liquid Reaction Of mentioning
confidence: 99%
See 1 more Smart Citation
“…22,23) It is also suggested that the chemical reaction from non-FM reactants (Bi + Mn) to FM products (MnBi) was greatly enhanced by magnetic field, increasing the amount of FM products. [24][25][26][27][28] At 523 K, which is lower than that melting point (544 K) of Bi, it was found that MnBi phase was not produced efficiently from Mn and Bi powders by zerofield heat treatment (solid-state reactive sintering), but magnetically oriented MnBi was produced by IFHT. [24][25][26][27] Furthermore, the production of magnetically oriented MnBi increased with increasing magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] At 523 K, which is lower than that melting point (544 K) of Bi, it was found that MnBi phase was not produced efficiently from Mn and Bi powders by zerofield heat treatment (solid-state reactive sintering), but magnetically oriented MnBi was produced by IFHT. [24][25][26][27] Furthermore, the production of magnetically oriented MnBi increased with increasing magnetic field. Since the liquidphase reaction is very fast even in zero magnetic field, the amount of MnBi synthesized did not depend on magnetic field intensity, but the MnBi crystals in the IFHT samples were oriented along the field direction.…”
Section: Introductionmentioning
confidence: 99%